Quantifying High-Performance Material Microstructure Using Nanomechanical Tools with Visual and Frequency Analysis - Sandoz-Rosado, Emil (Scanning, 2018)
High-performance materials like ballistic fibers have remarkable mechanical properties owing to specific patterns of organization ranging from the molecular scale, to the micro scale and macro scale. Understanding these strategies for material organization is critical to improving the mechanical properties of these high-performance materials. In this work, atomic force microscopy (AFM) was used to detect changes in material composition at an extremely high resolution with transverse-stiffness scanning. New methods for direct quantification of material morphology were developed, and applied as an example to these AFM scans, although these methods can be applied to any spatially-resolved scans. These techniques were used to delineate between subtle morphological differences in commercial ultra-high-molecular-weight polyethylene (UHMWPE) fibers that have different processing conditions and mechanical properties as well as quantify morphology in commercial Kevlar®, a high-performance material with an entirely different organization strategy. Both frequency analysis and visual processing methods were used to systematically quantify the microstructure of the fiber samples in this study. These techniques are the first step in establishing structure-property relationships that can be used to inform synthesis and processing techniques to achieve desired morphologies, and thus superior mechanical performance.